Displacement assay detection by a dimeric lanthanide luminescent ternary Tb(iii)-cyclen complex: High selectivity for phosphate and nitrate anions - CAFFREY, DAVID; GUNNLAUGSSON, THORFINNUR (My University, 2014)
The luminescent dimeric ternary lanthanide–cyclen complexes (2-(Ln.1)2; Ln = Tb/Eu) were designed and both their self-assembly formation and their ability to detect anions via displacement assays were investigated using spectrophotometric titrations in MeOH solution. The formation of 2-(Tb.1)2 and 2-(Eu.1)2 was investigated in solution, and determination of the binding constants and stoichiometry showed that the former was formed almost exclusively over the 1 : 1 complex 2-(Tb.1) after the addition of two equivalents of 2; while for 2-(Eu.1)2 a mixture of both stoichiometries existed even after the addition of four equivalents of 2. Of these two systems, 2-(Tb.1)2 was studied in details as a probe for anions, where significant changes where observed in the photophysical properties of the complex; with the characteristic Tb(III)-centred emission being fully switched off upon the sensing of phosphates and nitrate, giving rise to the formation of a H2PO4−:Tb.1 complex in a 1 : 2 stoichiometry upon sensing of H2PO4− by 2-(Tb.1)2, while NO3− gave 1 : 1 complex formation and two equivalents of NO3−·Tb.1
PUBLISHED
Keywords: luminescent dimeric ternary lanthanide–cyclen complex; luminescent dimeric ternary lanthanide–cyclen complex